Queer quit: a pilot study of a smoking cessation programme tailored to gay men - Dickson-Spillmann, Maria (BioMed Central, 2014)
BACKGROUND: The prevalence of cigarette smoking among adult gay males is higher than that of heterosexuals. There is a need for interventions adapted to gay culture. We conducted a pilot study using a modified version of a British smoking intervention programme tailored to gay men in Switzerland. As the main outcome, we assessed point prevalence smoking abstinence six months following programme attendance. METHODS: Seventy gay smokers attended seven weekly sessions in groups (median size = 5) taught by gay facilitators. A quit day was set in session 3. Integral components of the intervention were: discussing nicotine replacement therapy, performing carbon monoxide tests and forming ‘quit teams’. Seven-day point prevalence smoking abstinence, mental and physical health and the frequency of alcohol and drug use were assessed at baseline, in session 7 and at a six-month follow-up. RESULTS: Point prevalence abstinence significantly increased throughout the study (p = .00). At six months, 20 participants (28.6%) reported smoking abstinence over the previous 7 days. We observed increases in participants’ mental health between baseline and the six-month follow-up (p = .00). Participants who dropped out during the programme or were lost to follow-up smoked more cigarettes and were more nicotine dependent than the participants who were retained throughout the study duration (p ≤ .05). CONCLUSIONS: This smoking cessation programme for gay men produced rates of point prevalence abstinence that were similar to interventions for non-gay groups. The programme presented an opportunity for gay men to quit smoking and interact with other gay non-smokers. Our results confirm the need to test this programme more systematically with a view toward implementing it on a larger scale in Switzerland. TRIAL REGISTRATION: Current Controlled Trials ISRCTN36851118 (02 October 2013).